Directed Motivational Currents in L2: A focus on triggering factors, initial conditions, and (non)defining features. (November 2022) - Başöz, Tutku; Gümüş, Özge
Abstract: Recent trends in the field of L2 learning motivation have led to a proliferation of studies that examine Directed Motivational Currents (DMCs). However, there remains a paucity of evidence on the factors that trigger the launch of DMCs and previous research findings into the central components of DMCs have been contradictory. This qualitative study addresses these gaps by looking at the possible parameters that trigger DMCs, and examining the initial conditions necessary for the launch of DMCs, and the (non)defining core features of it. Semi-structured interviews were conducted with 27 EFL learners pursuing a bachelor's degree in Turkey. The factors triggering learners' DMCs were negative emotion, emergent opportunity, single and explicit goal, good teacher/classmates/motivating class group, moments of realization, a sense of achievement, a passion/interest for something, element of competition, external pressure, a big life decision, vision, outcome led, belief that the work had real value, and inspiring experience. Perceived behavioural control and challenge-skill balance were two initial conditions necessary for DMCs to begin. Goal orientedness, salient facilitative structure, and positive emotionality were found to be the core features of DMCs. The findings offer significant implications for how teachers could exploit these motivational surges to promote learning in EFL settings. Highlights: Goal orientedness is a prerequisite for Directed Motivational Currents. A facilitative structure has a key role in sustaining the unique motivational surge. Positive emotionality is another characteristic of Directed Motivational Currents. Perceived behavioral control is a base condition for Directed Motivational Currents. Challenge-skill balance is a base condition for Directed Motivational Currents.